2023
DOI: 10.1159/000529410
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Safety and Efficacy of Intravitreal Brolucizumab Injections for Neovascular Age-Related Macular Degeneration: A Multicenter Retrospective Real-World Study

Abstract: Introduction: To determine the short-term real-world safety and efficacy of intravitreal brolucizumab injections in Korean patients with neovascular age-related macular degeneration (nAMD). Methods: This multicenter retrospective study involved 294 eyes (treatment naïve 20 eye (6.8%) and non-treatment naïve 274 eyes (93.2%)) of 290 patients from 13 hospitals or retinal centers in South Korea. Patients with nAMD who received brolucizumab injection(s) between April 1 and November 30, 2021, with a follow-up ≥1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…First, the study evaluated data from Japanese patients and these findings may or may not be relevant to similar races/ethnicities. The observed incidence of IOI was comparable to that reported in Korea, 26 suggesting potential similarities in these populations. Nevertheless, these results may not necessarily be generalizable to other ethnic groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, the study evaluated data from Japanese patients and these findings may or may not be relevant to similar races/ethnicities. The observed incidence of IOI was comparable to that reported in Korea, 26 suggesting potential similarities in these populations. Nevertheless, these results may not necessarily be generalizable to other ethnic groups.…”
Section: Discussionsupporting
confidence: 83%
“…In a multicenter retrospective report of 294 eyes of Korean patients, the incidence of IOI was 13.9%. 26 Thus, the incidence of IOI seems to be higher in East Asian populations than in the American population. In addition, based on the findings of this study, which provides the most reliable information for Japanese nAMD patients to date, we can summarize the findings as follows: IOI is most common after the first IVBr injection, with its incidence concentrated and gradually decreasing in the first 4 months after the last injection.…”
Section: Discussionmentioning
confidence: 99%
“…Brolucizumab-associated IOI was reported to range from mild iritis/vitritis to severe retinal vasculitis with/without vascular occlusion and irreversible vision loss [ 48 , 49 ]. Although the HAWK and HARRIER trials reported higher rates of IOI with brolucizumab (4.6%) than with aflibercept, some clinical studies showed a higher incidence of IOI ranging between 13.9% and 19.0% [ 45 , 50 ]. In our study, the incidence of IOI is 6.3%.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of eyes with fluid in each of the intraretinal, subretinal, and sub-RPE compartments decreased following treatment with brolucizumab (Table 1D). The percentage of eyes with IRF in the fovea decreased from 30…”
Section: Fluid Resolution Analysismentioning
confidence: 96%